Modifications of the optical properties for DAM-ADC nuclear track detector exposed to alpha particles. (May 2018) - Rammah, Y.S.; Awad, E.M.
Abstract: Modifications of the optical properties of diallyl maleate-allyl diglycol carbonate (DAM-ADC) nuclear detector induced by alpha particles are described. DAM-ADC samples were irradiated perpendicularly by thin 241 Am disk source that emits alpha particles with 5.48 MeV. The optical absorption has been measured using the ultraviolet-visible (UV-1100) spectroscopy. It was found that DAM-ADC polymer shows substantial modifications in its optical characteristics upon irradiated with alpha particles with different energies. The optical energy band gap (Egap ) for the detector was calculated for the direct and the indirect allowed transitions in K -space using two approaches (Tauc ' s model and absorption spectrum fitting (ASF) method). Urbach's energy (Ea ), number of carbon atoms per conjugated length (N), number of carbon atoms per cluster (M), and refractive index (n) for the present samples were determined. Results reveal that the values of energy gap in direct transition are greater than those of indirect, before and after irradiation. (Egap ), (Ea ), (N), (M), and (n) of the present samples are changed significantly with irradiation time and value of alpha energy. Results reflect the possibility of using DAM-ADC polymer track detectors to estimate alpha particle energies using the variation of the absorbance. Highlights: DAM-ADC detectors have been irradiated with alpha particles with different energies. UV–visible spectra has been studied. Urbach's energy and energy band gaps have been calculated. Number of carbon atoms per conjugate length and cluster have been calculated.